2017
DOI: 10.1007/s00289-017-2113-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mineral filler additives on flammability, processing and use of silicone-based ceramifiable composites

Abstract: The aim of this work is to describe the changes in the properties of ceramifiable silicone rubber-based composites caused by the incorporation of novel alternative minerals in comparison to other popular, widely utilized fillers. TiO 2 , calcined kaolin and calcium-based minerals mix (CbMix) consisting of CaO (6.26 wt%), CaCO 3 (26.18 wt%) and Ca(OH) 2 (67.56 wt%) have not been considered as a dispersed phase of ceramifiable silicone composites destined for wire covers yet. Mineral fillers: TiO 2 (anatase), mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It is reported that in fireaccidents, the ceramics formed at high temperatures can resist propagation of flame, further combustion and strong water mist in fire extinguishing 9,10 . The ceramifiable silicone rubber is now commonly prepared by adding skeleton‐fillers like silicates, melting agents, dispersant agents and other additives to silicone rubber 4,9,11,12 . In 1978, Yajima et al synthesized SiC fiber with high tensile strength through polysiloxane precursor, which was widely used and industrialized in 1983 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that in fireaccidents, the ceramics formed at high temperatures can resist propagation of flame, further combustion and strong water mist in fire extinguishing 9,10 . The ceramifiable silicone rubber is now commonly prepared by adding skeleton‐fillers like silicates, melting agents, dispersant agents and other additives to silicone rubber 4,9,11,12 . In 1978, Yajima et al synthesized SiC fiber with high tensile strength through polysiloxane precursor, which was widely used and industrialized in 1983 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many achievements in the research on the formulation and processing of ceramizable silicone rubber composites [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], but research on the ceramization process and mechanism is not enough. Hanu et al [ 1 , 2 , 3 ] researched the ceramization mechanism of mica/silicone rubber composites, and put forward that ceramization was a process where the edge of mica melted and reacted with silica, which was the residue of silicone rubber, and the liquid phase connected the fillers and improved the residual strength.…”
Section: Introductionmentioning
confidence: 99%
“…Basalt fibres were proven to be an environmentally friendly and promising additive to polymer, metallic, and concrete composites [19], however its impact on the toxicity has not been presented yet. The problem of the emission of toxic gases during their decomposition is of key importance from the point of view of fire safety [20,21,22,23,24,25,26] if we take into consideration that ceramizable composites are at present more and more commonly used as an insulation material for wires that are intended for supplying power to electrical devices in huge malls, on the boards of planes, or in lifts. An earlier article presents the effect of basalt fillers on the thermal properties and flammability of silicone rubber composites, including ceramizable composites [27].…”
Section: Introductionmentioning
confidence: 99%